Making change last? Exploring the value of sustainability approaches in healthcare: a scoping review - L. Lennox; A. Linwood-Amor; L. Maher; J. Reed (BMC, 2020)
Abstract Background Numerous models, tools and frameworks have been produced to improve the sustainability of evidence-based interventions. Due to the vast number available, choosing the most appropriate one is increasingly difficult for researchers and practitioners. To understand the value of such approaches, evidence warranting their use is needed. However, there is limited understanding of how sustainability approaches have been used and how they have impacted research or practice. This review aims to consolidate evidence on the application and impact of sustainability approaches in healthcare settings. Methods A systematic scoping review was designed to search for peer-reviewed publications detailing the use of sustainability approaches in practice. A 5-stage framework for scoping reviews directed the search strategy, and quality assessment was performed using the Mixed Method Appraisal Tool. Searches were performed through electronic citation tracking and snowballing of references. Articles were obtained through Web of Science, PubMed and Google Scholar. Six outcome variables for sustainability were explored to ascertain impact of approaches. Results This review includes 68 articles demonstrating the application of sustainability approaches in practice. Results show an increase in the use of sustainability approaches in peer-reviewed studies. Approaches have been applied across a range of healthcare settings, including primary, secondary, tertiary and community healthcare. Approaches are used for five main purposes, namely analysis, evaluation, guidance, assessment and planning. Results outline benefits (e.g. improved conceptualisation of sustainability constructs and improved ability to interpret sustainability data) and challenges (e.g. issues with approach constructs and difficulty in application) associated with using a sustainability approach in practice. Few articles (14/68) reported the sustainability outcome variables explored; therefore, the impact of approaches on sustainability remains unclear. Additional sustainability outcome variables reported in retrieved articles are discussed. Conclusions This review provides practitioners and researchers with a consolidated evidence base on sustainability approaches. Findings highlight the remaining gaps in the literature and emphasise the need for improved rigour and reporting of sustainability approaches in research studies. To guide future assessment and study of sustainability in healthcare settings an updated list of sustainability outcome variables is proposed. Trial Registration This review was registered on the PROSPERO database CRD 42016040081 in June 2016.